Sakai Magara: Activist Girl of Early Twentieth Century Japan. Issue 2 (1st June 2020) - Hartley, Barbara
Abstract: In this article, I profile the activism of 18-year-old Sakai Magara (1903–1985). I focus in particular on her role in the Sekirankai (Red Wave Society), which was a short-lived women's political organization formed in April 1921 and aligned directly with socialist and anti-capitalist worker issues. My discussion draws on three principal sources: contemporaneous accounts of the Society; writings by women with whom Magara collaborated; and the words of Magara herself. I pay attention to Magara's contribution to Sekirankai, the influences on the development of her activism, and the barriers to political participation by girls and women in Japan.